Perbandingan rope jump, step up, dan diagonal cone terhadap power dan kelincahan - Furqoni, Randi Sofyan; Sudijandoko, Andun (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
This study aims: (1) to determine the effect of rope jump training on increasing leg muscle power and agility; (2) to determine the effect of step-up training on increasing leg muscle power and agility 3) to determine the effect of diagonal cone hops exercises on increasing leg muscle power and agility; and (4) to find out the differences in the effect of pliometric rope jump, step up, and diagonal cone hops exercises on increasing leg muscle power and agility. The sample of this study was 40 students of futsal extracurricular at Firdaus Jembrana High School. This type of research is quantitative research with a quasi-experimental method. The study design used a pre-test and post-test non-randomized control group, with data analysis using MANOVA. The process of collecting data was to use leg muscle power tests by using jump df and agility tests using the agility T-test during the pre-test and post-test. Then the research data were analyzed using SPSS ver 16.0. It can be concluded that there is an increase in limb muscle power and agility for each group after being given training with a significant value <0.05 in the paired sample t-test. Increased limb muscle power by 12% and 1% agility in rope jump training, 5% increase in leg muscle power and 1% agility in step-up exercises, and increased leg muscle power by 8% and 2% agility in diagonal cone hops exercises.